Cloning attack on a Proxy Blind Signature Scheme over Braid Groups - Kumar, Manoj (International Journal of Computer Sciences and Engineering, 2019)
Proxy blind signature scheme is a combination proxy signature and blind signature scheme. Verma proposed a proxy blind signature scheme over braid groups and claimed that his scheme is secure against all possible security lapses and also satisfy all essential security attributes. This paper analyzes Verma’s proposed scheme and found that this scheme suffers with the serious security vulnerabilitie: cloning attack.